1988
DOI: 10.1164/ajrccm/138.5.1220
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Exposure and Lung Disease in Tungsten Carbide Production: A Cross-sectional Study of Current Workers

Abstract: A cross-sectional study of 1,039 tungsten carbide (TC) production workers was carried out. The purposes were (1) to evaluate the prevalence of interstitial lung disease (ILD) and work-related wheezing, (2) to assess correlations between cobalt exposure and pulmonary disease, (3) to compare lung disease in grinders of hard carbide versus nongrinders, and (4) to evaluate the effects of new and previous threshold limit values for cobalt of 50 and 100 micrograms/m3. We obtained medical and occupational histories, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(27 citation statements)
references
References 5 publications
0
23
0
4
Order By: Relevance
“…If Co particles in the presence of WC particles cause HMD via generation of ROS [4][5][6] , then our characterization of airborne particles may help to explain the inconsistent findings of epidemiological studies, e.g., between Meyer-Bisch et al 1) and Sprince et al 2) ; only Sprince et al 2) showed a higher risk in the later stages of the CTC manufacturing process. We observed that airborne particles potentially available for inhalation in spray drying and all subsequent work areas were a mixture of elemental tungsten and elemental Co particles and/or multi-constituent W/Co particles (ostensibly WC/Co particles, but the relative carbon contribution of the collection substrate and metal carbides is unknown).…”
Section: Airborne Particlesmentioning
confidence: 85%
“…If Co particles in the presence of WC particles cause HMD via generation of ROS [4][5][6] , then our characterization of airborne particles may help to explain the inconsistent findings of epidemiological studies, e.g., between Meyer-Bisch et al 1) and Sprince et al 2) ; only Sprince et al 2) showed a higher risk in the later stages of the CTC manufacturing process. We observed that airborne particles potentially available for inhalation in spray drying and all subsequent work areas were a mixture of elemental tungsten and elemental Co particles and/or multi-constituent W/Co particles (ostensibly WC/Co particles, but the relative carbon contribution of the collection substrate and metal carbides is unknown).…”
Section: Airborne Particlesmentioning
confidence: 85%
“…If occupational asthma is caused by exposure to particles with aerodynamic sizes capable of depositing in the tracheobronchial, bronchial, and alveolar regions of the lung and with chemical composition that contains cobalt (alone or in the presence of tungsten carbide), then our air-monitoring results in conjunction with in vitro dissolution test results may help to explain why cases of occupational asthma are observed among workers who handle pre-sintered hard metal powders and grind and manipulate sintered CTC parts (Davison et al, 1983;Sprince et al 1988;Meyer-Bisch et al, 1989;Shirakawa et al, 1989;Kusaka et al, 1996) and among diamond polishers whose only exposure is to cobalt (Gheysens et al, 1985). Consistent with these studies, we observed exposures to cobalt in all work areas spanning powder production to handling finished product parts.…”
Section: Occupational Asthmamentioning
confidence: 99%
“…If HMD and lung cancer are caused by alveolar deposition of respirable-size particles that contain cobalt associated with tungsten, then our air monitoring exposure data may help to understand lung cancer and explain why HMD is observed among workers exposed to pre-sintered material alone (Meyer-Bisch et al, 1989), post-sintered CTC material alone (Sprince et al, 1988), and both pre-and post-sintered materials (Bech et al, 1962;Coates and Watson, 1971;Sjo¨gren et al, 1980;Davison et al, 1983;Sprince et al, 1984;Cugell et al, 1990;Figueroa et al, 1992;Fischbein et al, 1992). Consistent with these studies, we observed that workers were co-exposed to respirable cobalt-and tungstencontaining particles in all work areas (see Tables 4 and 5) spanning powder production (pre-sintered materials) through handling final product parts (post-sintered materials).…”
Section: Hard Metal Disease and Lung Cancermentioning
confidence: 99%
See 2 more Smart Citations